THE CLINICAL EXAMINATION- LONG CASE THE MOST VALID TEST IN A MEDICAL SCHOOL - Mirghani, Omer Ahmed; Elsanousi, Mohammed (Gezira Journal of Health Sciences, 2009)
This article includes (1) the basic contents of a clinical examination long case (ii) the strengths of the examination which justify labeling it as the most valid (iii) guidelines for conduction of the examination (iv) guidelines for marking (v) the place of the short case and Objective Structured Clinical Examination (OSCE) in the end of course examination.